The Impact of Travel Motivations on Destination Loyalty: The Mediating Role of Tourist Satisfaction among Russian Tourists in Post-Pandemic Sri Lanka - Prageeth Niroshan; Nisha Jayasuriya; Heshan Sameera Kankanam Pathiranage (ASEAN Journal on Hospitality and Tourism, 2026)
The recovery of global tourism after COVID-19 has renewed interest in understanding international tourists' motivations and behavioral intentions. This study investigates how push and pull travel motivations influence tourist satisfaction and destination loyalty among Russian tourists visiting Sri Lanka in the post-pandemic period. Data were collected from 384 Russian tourists and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that both push motivations (β = 0.165, p < 0.01) and pull motivations (β = 0.662, p < 0.001) significantly enhance tourist satisfaction. However, destination loyalty is primarily driven by push motivations, while pull motivations influence loyalty indirectly through satisfaction. The mediation analysis confirms that tourist satisfaction plays a critical mediating role in translating travel motivations into loyalty intentions. This study contributes to tourism literature by extending push–pull motivation theory in a post-pandemic context and provides practical insights for Sri Lankan tourism policymakers and destination marketers seeking to strengthen tourist retention and repeat visitation.